2015
DOI: 10.1002/etc.3218
|View full text |Cite
|
Sign up to set email alerts
|

Defining the role of omics in assessing ecosystem health: Perspectives from the Canadian environmental monitoring program

Abstract: Scientific reviews and studies continue to describe omics technologies as the next generation of tools for environmental monitoring, while cautioning that there are limitations and obstacles to overcome. However, omics has not yet transitioned into national environmental monitoring programs designed to assess ecosystem health. Using the example of the Canadian Environmental Effects Monitoring (EEM) program, the authors describe the steps that would be required for omics technologies to be included in such an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 137 publications
(176 reference statements)
0
38
0
Order By: Relevance
“…Ideally, molecular responses would be extrapolated to predict effects on higher biological levels. The link is however complicated by a lacking understanding of how baseline gene expression patterns vary with, for example, species, sexes, developmental stages, and seasons (Bahamonde et al 2016;Fent and Sumpter 2011). Although not always addressed, understanding the variation is thus necessary to discern actual responses from the background noise, for meaningful interpretation of transcriptional data and for successful integration into molecular biomarker panels (Bahamonde et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, molecular responses would be extrapolated to predict effects on higher biological levels. The link is however complicated by a lacking understanding of how baseline gene expression patterns vary with, for example, species, sexes, developmental stages, and seasons (Bahamonde et al 2016;Fent and Sumpter 2011). Although not always addressed, understanding the variation is thus necessary to discern actual responses from the background noise, for meaningful interpretation of transcriptional data and for successful integration into molecular biomarker panels (Bahamonde et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out by Bahamonde et al [79], environmental factors such as temperature, flows, microhabitat use, and/or nutrient availability may be important in altering gene expression across years and sites. However, the number of differentially expressed probes was not affected by the changes in effluent quality at either of the studied sites.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that factors characteristic of individual years are affecting the number of genes that are differently expressed. As pointed out by Bahamonde et al [79], environmental factors such as temperature, flows, microhabitat use, and/or nutrient availability may be important in altering gene expression across years and sites. However, gene set enrichment analysis and subnetwork enrichment analysis may be more sensitive types of analyses (compared with the number of differentially expressed probes) when it comes to interpreting gene patterns changes in response to MWWTP effluent exposure.…”
Section: Discussionmentioning
confidence: 99%
“…These investigations take a targeted approach to explore effects on pathways likely affected by adaptation (Clark & Di Giulio, 2012; Oziolor et al., 2016b). On the other hand, with top‐down ‐omics approaches, understanding of transcriptomic, metabolomic, and proteomic differences in responsiveness and basal levels in adapted populations may inform possible fitness costs in a much more thorough manner (Bahamonde, Feswick, Isaacs, Munkittrick, & Martyniuk, 2016; Bundy, Davey, & Viant, 2008; Monsinjon & Knigge, 2007). One example is a comparative transcriptomic approach that finds altered responsiveness in biocide resistant Salmonella enterica Typhimurium that further explain increased sensitivity of this strain to other antimicrobials (Curiao et al., 2016).…”
Section: Other ‐Omics and Evolutionary Toxicologymentioning
confidence: 99%